The farm as an educative tool in the development of place attachments among Irish farm youth. Issue 3 (4th May 2017) - Cassidy, Anne
ABSTRACT: This paper focuses on the educative role of the farm in the development of relationships between young people and the homeplace they grew up on. The paper is based on qualitative interviews with a cohort of 30 Irish university students (15 men and 15 women) brought up on Irish family farms who would not become full-time farmers. The farm acts as an educational tool through which broader cultural and familial norms of land ownership, succession and affiliations with the land are transmitted to the next generation. This is manifested through, for example, the creation of foundational stories about their forebearers' influence on the physical appearance of the farm. The resulting place attachments are of profound depth and serve a key role in the succession process in helping to build a sense of duty and responsibilisation into the next generation's relationship with the landholding.